2022
DOI: 10.1093/g3journal/jkac014
|View full text |Cite
|
Sign up to set email alerts
|

Formation and function of dauer ascarosides in the nematodes Caenorhabditis briggsae and Caenorhabditis elegans

Abstract: The biosynthetic pathways and functions of ascaroside signaling molecules in the nematode Caenorhabditis elegans have been studied in order to better understand complex, integrative developmental decision-making. Although it is known that ascarosides play multiple roles in the development and behavior of nematode species other than C. elegans, these parallel pheromone systems have not been well-studied. Here, we show that ascarosides in the nematode Caenorhabditis briggsae are biosynthesized in the same manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…S1c, d). Dauer larvae can be identified by their growth arrest and distinct morphology characterized by specialized cuticular structures called alae, a constricted pharynx, arrested germ line, decreased pharyngeal pumping rates, and detergent (1% SDS) resistance (3)(4)(5)(6)(7)(8)(9). ilc-17.1(syb5296)X dauer larvae displayed all these features (Supplementary Fig.…”
Section: Ilc-171 Is Released By C Elegans Amphid Neurons In Response ...mentioning
confidence: 99%
See 4 more Smart Citations
“…S1c, d). Dauer larvae can be identified by their growth arrest and distinct morphology characterized by specialized cuticular structures called alae, a constricted pharynx, arrested germ line, decreased pharyngeal pumping rates, and detergent (1% SDS) resistance (3)(4)(5)(6)(7)(8)(9). ilc-17.1(syb5296)X dauer larvae displayed all these features (Supplementary Fig.…”
Section: Ilc-171 Is Released By C Elegans Amphid Neurons In Response ...mentioning
confidence: 99%
“…1g). This suggested that the role of ILC-17.1 signaling in dauer might be related to food, a prominent modulator of the dauer decision (3)(4)(5)(6)(7)(8)(9), and that the ILC-17.1 ligand, and perhaps not the ILCR-2 receptor per se, could be responsive to the food signals.…”
Section: Ilc-171 Is Released By C Elegans Amphid Neurons In Response ...mentioning
confidence: 99%
See 3 more Smart Citations